A cross sectional survey on COVID-19 vaccination coverage at urban health center of a district in central Gujarat - Sheth, Margi B.; Kalariya, Gopi K.; Makwana, Bharati L.; Shringarpure, Kalpita S. (International Journal Of Community Medicine And Public Health, 2023)
Background: COVID-19 vaccination can lead to herd immunity when a sufficient proportion of population is vaccinated. Effectiveness of vaccination coverage depends on the population’s willingness to be vaccinated completely. Aim and objective was to estimate COVID-19 vaccination coverage and to determine reasons for its acceptance and non-acceptance in urban field practice area of medical college attached with tertiary care hospital. Methods: A cross-sectional house to house survey was conducted among the households (n=1346) under an urban health training centre (UHTC) of a medical college in central Gujarat after the second wave of COVID-19. All the beneficiaries above the age of 18 years residing in the house-holds coming under the field area were included in the study. The data was collected using Epi-collect 5 mobile based applications. Beneficiaries who had taken two doses of COVID-19 vaccine were counted as fully immunized. Vaccination coverage was calculated different for first and second dose. Facilitators and barriers for COVID-19 vaccination were shown with appropriate diagram. Results: Out of the 1832 participants in the survey, vaccination coverage was 78.22% for first dose and 37.23% for second dose. Most common motivation (81%) behind taking vaccination was “good health”. Among the non-users for COVID-19 vaccination, 36.8% did not take the vaccine due to fear of adverse reactions. Conclusions: Vaccination coverage is average in the urban area surveyed. Majority of the population is motivated to take the vaccine to protect themselves from COVID-19. The main reason for not taking vaccine was fear of side-effect of vaccine.